Scaling of energy characteristics of polycrystalline laser at room temperature. (September 2015) - Gavrishchuk, E.M.; Ikonnikov, V.B.; Kazantsev, S.Yu.; Kononov, I.G.; Rodin, S.A.; Savin, D.V.; Timofeeva, N.A.; Firsov, K.N.
Abstract: The lasing characteristics of lasers based on diffusion-doped polycrystalline samples excited at room temperature by an electric-discharge HF laser are studied. A sample doped from two sides (working surfaces) emitted laser radiation with the energy with the slope efficiency and the efficiency with respect to the absorbed energy in the case of an elliptical pump spot of size . It is found that the possibility of increasing the lasing energy of the samples of these types by increasing the pump spot area (at a constant pump energy density) is limited by the appearance of parasitic generation typical for disk lasers. The first results are reported on the laser based on a polycrystalline sample made by a technology that allows one to form a zero dopant concentration on the surface and a maximum concentration inside the sample (i.e., to create a sample with internal doping). The possibilities of increasing the laser energy at room temperature by using multilayer samples fabricated by this doping method are discussed.